A trend analysis on the licensure examination success of teacher education program of a state university - Pelayo, Elmira Thrina C.; Gloria, Daianne S.; Hero, Jesson L. (Journal of Education and Learning (EduLearn), 2026)
The 21st-century education paradigm and Sustainable Development Goal (SDG) 4 aimed to produce and supply highly calibrated and qualified teachers. A professional teacher should pass the licensure examination to become a full-fledged professional teacher. However, licensure examination is one of the hurdles for beginning teachers, and failing rates were still observed among universities and colleges in the Philippines. Hence, this study aimed to evaluate the licensure examination success of teacher education graduates in one state university in the City of Malolos, Bulacan covering the years of 2019, 2022, and 2023. This study utilized quantitative trend analysis to determine the trends and success of licensure examination of the stated years. The data revealed that the trend and patterns of licensure examination for teachers (LET) results of beginning teachers for the three consecutive years are above the national passing percentage of 75% and described as satisfactory. The beginning teachers’ satisfactory results produce a significant difference in the following: examination year, elementary education area of concentration, secondary education area of concentration, and examination components. Thus, the strengthening and enhancing the existing curricular and pre-board examination program should be intensified and reinforced to sustain and uplift the university’s standing in terms of success rate.